2017
DOI: 10.1016/j.ymthe.2017.03.035
|View full text |Cite|
|
Sign up to set email alerts
|

Preclinical and Clinical Demonstration of Immunogenicity by mRNA Vaccines against H10N8 and H7N9 Influenza Viruses

Abstract: Recently, the World Health Organization confirmed 120 new human cases of avian H7N9 influenza in China resulting in 37 deaths, highlighting the concern for a potential pandemic and the need for an effective, safe, and high-speed vaccine production platform. Production speed and scale of mRNA-based vaccines make them ideally suited to impede potential pandemic threats. Here we show that lipid nanoparticle (LNP)-formulated, modified mRNA vaccines, encoding hemagglutinin (HA) proteins of H10N8 (A/Jiangxi-Donghu/3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
482
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 546 publications
(527 citation statements)
references
References 55 publications
(77 reference statements)
12
482
1
7
Order By: Relevance
“…Engineering of the RNA sequence has rendered synthetic mRNA more translatable than ever before. Highly efficient and non-toxic RNA carriers have been developed that in some cases 21,22 allow prolonged antigen expression in vivo (TABLE 1). Some vaccine formulations contain novel adjuvants, while others elicit potent responses in the absence of known adjuvants.…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
See 3 more Smart Citations
“…Engineering of the RNA sequence has rendered synthetic mRNA more translatable than ever before. Highly efficient and non-toxic RNA carriers have been developed that in some cases 21,22 allow prolonged antigen expression in vivo (TABLE 1). Some vaccine formulations contain novel adjuvants, while others elicit potent responses in the absence of known adjuvants.…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
“…81), but it has only recently been shown that LNPs are potent tools for in vivo delivery of self-amplifying RNA 19 and conventional, non-replicating mRNA 21 . Systemically delivered mRNA–LNP complexes mainly target the liver owing to binding of apolipoprotein E and subsequent receptor-mediated uptake by hepatocytes 82 , and intradermal, intramuscular and subcutaneous administration have been shown to produce prolonged protein expression at the site of the injection 21,22 . The mechanisms of mRNA escape into the cytoplasm are incompletely understood, not only for artificial liposomes but also for naturally occurring exosomes 83 .…”
Section: Recent Advances In Mrna Vaccine Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…In this approach, synthetic mRNAs are formulated with lipid nanoparticles to enhance processing and immunogenicity. There has been a phase I study of an mRNA-based influenza vaccine developed using this technology, and the vaccine was shown to be safe and highly immunogenic in 23 volunteers immunized in the context of an ongoing double-blind, placebo-controlled, dose-escalating trial (87). Moderna Vaccines has recently announced that preclinical development of a six-component CMV mRNA vaccine, mRNA-1647, will commence.…”
Section: Nucleic Acid-based CMV Vaccinesmentioning
confidence: 99%